Bathyal Mollusca from the cold-water coral biotope of Santa Maria di Leuca (Apulian margin, southern Italy) - Negri, Mauro Pietro; Corselli, Cesare (Zootaxa, 2016)
This paper describes 97 molluskan species (45 Bivalvia, 3 Scaphopoda, 49 Gastropoda) recovered from bathyal bottoms off Santa Maria di Leuca (Puglia, Italy), in the northern Ionian Sea, and provides data about their taxonomy, geographical distribution, habitat, ecological requirements and fossil record. Only 6 species remain unidentified, and all are illustrated. The bivalve-dominated assemblages belong to the so-called “cold-water coral ecosystem”. They appear to depend mainly on substrate characteristics, with faunas related to hard substrate around coral-colonized mound tops, and mud-related ones in inter-mound areas, respectively. Nuculanoida and Pectinoidea among bivalves, and Conoidea and Pyramidelloidea among gastropods are the most diverse suprafamilial groups. The present paper is the first comprehensive taxonomic overview of Mediterranean bathyal mollusks including larval shell characters.